THE AUTOPHAGY-INDEPENDENT ROLE OF ATG7 IN REGULATING NEUROGENESIS (European Journal of Histochemistry)
Spinal cord injury (SCI) is a widespread neurological disease that can cause long-term disability. Although there is currently no effective clinical treatment, stem cells have great potential for repairing SCI. Stem cells are a group of cells with unique selfrenewal and differentiation abilities. To achieve cell remodeling, stem cell renewal and differentiation require strict control of protein turnover in the stem cells. Autophagy, a highly conserved «gatekeeper» of cell homeostasis, can regulate cell remodeling by precisely controlling protein turnover in cells. Recently, it has been found that the expression of autophagy markers changes in animal models of SCI. Therefore, understanding whether autophagy can affect the fate of stem cells and promote SCI repair is of considerable clinical value. To explore the role of autophagy or its key genes in activating neuronal differentiation of endogenous neural stem cells for SCI repair, it is necessary to use the traumatic mouse spinal cord injury model. Based on the relationship between autophagy homeostasis control and stem cell function, we are exploring new strategies to help repair spinal cord injury.